Extended long-term follow-up of metastatic melanoma patients treated with immunotherapy: late relapses and second primary melanomas - Minor, David R.; Kim, Kevin B.; Karuturi, R. Krishna M.; Kashani-Sabet, Mohammed (Frontiers in Oncology, 2023)
Background Immunotherapy has revolutionized the treatment of patients with advanced melanoma as well as other cancers. Most studies, whether of interleukin-2 or checkpoint inhibitor therapies, have limited follow-up past 5 years, making the incidence of late relapses uncertain. In addition, the incidence of second primary melanomas in patients with stage four melanoma treated with immunotherapy has rarely been reported.We performed a single-institution retrospective study of stage four melanoma patients treated with interleukin-2 or checkpoint inhibitors over the period from 1992-2013. We found 59 patients alive and in remission five years after beginning immunotherapy and reviewed their subsequent clinical course.This 59-patient cohort had a median follow-up of 13.1 years, with 36 patients who followed for at least 10 years. Four patients (6.8%) had relapses of their metastatic melanoma, at 5, 8, 15, and 17 years after starting successful immunotherapy. Three of the four are still alive.Only one patient in 690 patient-years of observation had a second primary invasive melanoma.Although late relapses after immunotherapy for melanoma do occur, we can conclude that the prognosis of stage four melanoma patients in continuous remission five years after starting immunotherapy is excellent, with a progression-free survival of approximately 85%, and a melanoma-specific survival of approximately 95% at 20 years in our series. Our incidence of second primary melanomas is lower than usually reported. These results have important implications regarding the follow up of stage IV melanoma patients successfully treated with immunotherapy.